Analysis of Sectoral Environmental Product Declarations as a Data Source for Life Cycle Assessment - María Seila Otero; Teresa Garnica; Soledad Montilla; Marta Conde; José A. Tenorio (Buildings, 2023)
The life cycle assessment (LCA) methodology is becoming increasingly prevalent in the quantification of the environmental status in the building sector following new legislative frameworks. Countries need to quantify and assess their environmental impacts as a previous step to regulation and decision-making. In this context, based on a consensus with manufacturers, standardized national data sets are being developed, referred to as sectoral environmental product declarations (EPDs). This study assesses these EPDs with the aim of providing relevant information for global decision-making, focusing on their consistency and shortcomings. An assessment was carried out at both the national level, considering all sectoral EPDs and declared products, and at the international level, with three common building materials (brick, steel, and concrete). The results highlight the lack of traceability in the development and assessment of uncertainty, resulting in substantial discrepancies in reported impacts, especially in the later stages of the life cycle (up to 90% difference). Meanwhile, impacts such as global warming potential or total renewable and non-renewable primary energy use show homogeneous values in the cradle-to-gate stages, with differences generally being under 10%. The analysis of sectoral EPDs should act as a guideline for designing buildings with environmental sustainability criteria, as the last section of this study attempts to highlight.